Percutaneous Ultrasound‐Guided Aspiration of an Anterior Cruciate Ligament Ganglion Cyst: Description of Technique and Case Presentation. Issue 12 (1st August 2014) - Krill, Michael; Peck, Evan
Abstract : An anterior cruciate ligament ganglion cyst is an infrequent but potentially clinically significant cause of knee pain. Although the cyst may be removed surgically, percutaneous ultrasound‐guided anterior cruciate ligament ganglion cyst aspiration and injection is feasible. To our knowledge, we present the first reported case description of the utilization of ultrasound guidance to perform this procedure with a successful clinical outcome.